Pengaruh Model Pembelajaran Snowball Throwing Terhadap Minat Kelas III SDN Prapag Kidul 03 - Nurpratiwiningsih, Laelia; Inayah, Tanjali; Setiyoko, Didik Tri (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of the snowball throwing learning model on the interest of class III SDN Prapag Kidul 03 in Maths material theme 7 subtheme 2 "technology development" in the material of folding symmetry and rotational symmetry. The method used in this research is by experiment. The technique of taking cluster random sampling and the data for interest in learning is carried out with a self-assessment sheet in the form of a questionnaire for students. The materials used are folding symmetry and rotational symmetry materials. This study was analyzed using the t test. The results obtained were (1) The results of the pre-test of interest in learning mathematics on rotational symmetry and folding symmetry in the experimental class obtained an average value of 43.35 greater than the average value of the control class, namely 39.87. This t-test uses SPSS 24 software assistance. The results obtained using the t-test obtained a significance of 0.081 <0.05, which means that there is an effect of the snowball throwing model on learning interest, the hypothesis (Ha) is accepted (Ho) is rejected.